TIGIT Induces (CD3+) T Cell Dysfunction in Colorectal Cancer by Inhibiting Glucose Metabolism - Shao, Qi; Wang, Lei; Yuan, Maoling; Jin, Xiaohong; Chen, Zhiming; Wu, Changping (Frontiers in Immunology, 2021)
T-cell immunoglobulin and immunoreceptor tyrosine-based inhibitory motif domain (TIGIT) is an immunosuppressive receptor expressed on the surface of immune cells, suppressing immune responses by activating the intracellular negative regulatory signals. TIGIT plays an important role in the pathogenesis of various tumors, but its immune escape in colorectal cancer remains unclear. We found that the proportion of CD3+TIGIT+ T cells was increased in peripheral blood and cancer tissue in colorectal cancer patients when compared with the healthy donors. These cells exhibited functional defects, low proliferative activity, impaired cytokine production and reduced glucose metabolism. A strong association was also observed between the elevated TIGIT expression and poor prognosis in this cohort. In the in vitro co-culture assays of T cells and tumor cells, the suppressed glucose metabolic activity of T cells was reversed by TIGIT blockade. In addition, this blockade induced the apoptosis and reduced G2/M transit in tumor cells. The antitumor efficacy of TIGIT Ab therapy was further demonstrated in a human colorectal xenograft mice model while co-blockers of TIGIT and PD-1 exhibited synergistic suppressing effects on tumor growth. These results suggest that while TIGIT induces CD3+ T cell dysfunction in colorectal cancer, co-targeting TIGIT and PD-1 can lead to an effective antitumor response and may serve as a novel therapeutic strategy for colorectal patients.